Analysis of Strength and Weakness Management of Madrasah Aliyah Institutions: Analisis Strength dan Weakness Manajemen Lembaga Madrasah Aliyah - Maslacha, Khusanah Aniq; Istikomah, Istikomah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the strengths and weaknesses of MA Al-Machfudzoh, the manager or principal of the school in overcoming the weaknesses and obstacles that exist in the principal. This study uses a qualitative research method with a case study approach. The subjects of this research are the principal and the administrator of the foundation. Data collection techniques with observation, interviews and documentation. The data analysis technique uses data reduction, data display, and conclusions. The results of this study are aspects of the strength of MA Al-Machfudzoh, namely integrated with Islamic boarding schools, teacher qualifications according to the lessons taught, good cooperation between teachers and principals, discipline of teachers and employees, adequate infrastructure. While the weak aspects are that the school is still in the process of accreditation, the location is not strategic, there are still few graduates, the teaching staff does not have certification, and the class majors are still few. Managers or principals in overcoming weaknesses, namely evaluation evaluation. And the obstacles experienced by the principal are not being able to handle children who come out of the cottage.